x-4-2x=5+3(2x-4)

Simple and best practice solution for x-4-2x=5+3(2x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-4-2x=5+3(2x-4) equation:


Simplifying
x + -4 + -2x = 5 + 3(2x + -4)

Reorder the terms:
-4 + x + -2x = 5 + 3(2x + -4)

Combine like terms: x + -2x = -1x
-4 + -1x = 5 + 3(2x + -4)

Reorder the terms:
-4 + -1x = 5 + 3(-4 + 2x)
-4 + -1x = 5 + (-4 * 3 + 2x * 3)
-4 + -1x = 5 + (-12 + 6x)

Combine like terms: 5 + -12 = -7
-4 + -1x = -7 + 6x

Solving
-4 + -1x = -7 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-4 + -1x + -6x = -7 + 6x + -6x

Combine like terms: -1x + -6x = -7x
-4 + -7x = -7 + 6x + -6x

Combine like terms: 6x + -6x = 0
-4 + -7x = -7 + 0
-4 + -7x = -7

Add '4' to each side of the equation.
-4 + 4 + -7x = -7 + 4

Combine like terms: -4 + 4 = 0
0 + -7x = -7 + 4
-7x = -7 + 4

Combine like terms: -7 + 4 = -3
-7x = -3

Divide each side by '-7'.
x = 0.4285714286

Simplifying
x = 0.4285714286

See similar equations:

| 3d^2-7d=0 | | 29+4x=9x | | 12x+5x-6=28 | | uuu=2 | | 5x-3/2 | | -2x-15=x+9 | | 3=z/7.5 | | 4=z/7.3 | | 10x=12x+18 | | log(x-2)-log(2x-9)=0 | | 0.67x-12=18 | | 0/8x7 | | 12x+10=170 | | 3(-1/6)(-2/5)= | | 4+6=4+6 | | 11=-5+2x | | f(3a)=8x-6 | | 2a+b=5a+8b | | (-4)(-3)(-2)= | | 20/28=5/x | | 7n^3+49n=0 | | 3x+4=6x+8 | | 3(2+q)+15=q | | xsquared-5x=9 | | 1x+7y=36 | | f(x)=5x^5+x^4-27x^3-13x^2+134x+120 | | 3(-1/2)(-2/5 | | 0.2x+0.8= | | -4y=168 | | 0.5x+10=16 | | (x+7)+(3x-7)= | | 2/3•4 |

Equations solver categories